Evropské sdruzení pro zdravotnické informance a knihovny-- EAHIL/AEIBS - Spála, M; Choc, F; Pinkas, O (Sbornik lekarsky, 1994)
The authors give a short history of the association, beginning with its establishment (1986) and a survey of its activities up to the summer of 1994, and its organization. They write about conditions and terms of membership, about aims and objectives of the association: to improve co-operation among European medical libraries, to raise standards of library and information services as well as professionality of librarians and information officers and their continuous education, especially in regard to new technologies. The authors also emphasize the European character and principles of tolerance that enable a connection of medical nursing, veterinary and pharmaceutical libraries/librarians in these specializations in various countries. It is necessary for information users to learn modern library methods, including information skills for the learning process (libraries of medical faculties). No less important is the role of libraries for research and evaluation of research. A survey of Czechoslovak and Czech participation in EAHIL is also given here. The course of the Fourth European Conference of Medical and Health Libraries on Oslo (from 28th June to 2nd July, 1994) is shortly described. Further library conference activities are also mentioned: 7th International Congress of Medical Librarianship in Washington, DC, May 10-12, 1995; Fourth Nordic Conference for Medical Libraries, Copenhagen (Denmark), August 21-24, 1995; EAHIL Symposium on Cooperation of Medical Libraries, Prague (Czech Republic), September 21-22, 1995; Fifth European Conference of Medical and Health Libraries, Coimbra (Portugal), September 18-21, 1996.
Keywords: knihovnické spolky; Evropa; Library Associations; Libraries, Medical; Czech Republic; lékařské knihovny; Europe; Česká republika